Photochromic microcrystalline glass material with high energy storage efficiency and preparation method
By preparing microcrystalline glass materials with Ba[Ti(1-x)Ax]O3 main crystal phase and SiO2-Al2O3-B2O3 glass phase with cubic phase perovskite structure, the problem of insufficient energy storage density and stability in existing dielectric materials in high-pulse power systems is solved, and high-efficiency energy storage and ultraviolet radiation resistance are achieved, which is suitable for extreme environments.
Patent Information
- Application Number
- CN202510765460.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-10
- Publication Date
- 2025-08-22
AI Technical Summary
The existing dielectric materials have problems in high-pulse power systems with insufficient energy storage density and power density, and insufficient stability and resistance to ultraviolet radiation in extreme environments.
The crystal-crystalline glass materials with Ba[Ti(1-x)Ax]O3 main crystal phase and SiO2-Al2O3-B2O3 glass phase with cubic phase perovskite structure are used to form crystal-crystalline glass with nanocrystals through high-temperature melting, heat treatment and nucleation crystallization processes. Combined with the silver electrode preparation method, high energy storage efficiency and photochromic characteristics are achieved.
It has achieved high energy storage density, ultra-fast charging and discharging speed, high energy storage efficiency under high field strength and good ultraviolet radiation resistance, significantly improving the energy storage performance of microcrystalline glass dielectric materials and stability in extreme environments.
Smart Images

Figure CN120518320A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to dielectric energy storage materials, and in particular to a photochromic microcrystalline glass material with high energy storage efficiency and a preparation method thereof. Background Art
[0002] Physical capacitors, due to their ultra-fast charge and discharge speeds, high power density, and excellent chemical stability, are widely used in pulsed power systems such as capacitive ignition systems, new energy electric vehicles, pulsed power weapon systems, and medical CT scans. Dielectric materials, as a crucial component of physical capacitors, directly impact their energy storage performance. Currently, the main dielectric materials used in all-solid-state physical capacitors include ceramics, glass, microcrystalline glass, and polymer dielectric materials.
[0003] Although dielectric ceramic materials have a high dielectric constant and can achieve a higher energy storage density at a lower field strength, their long discharge time (on the order of microseconds) restricts the improvement of their power density, and their low breakdown field strength limits their application in high pulse power systems; glass dielectrics have an ultra-fast discharge speed, with a discharge time generally on the order of nanoseconds, but their low dielectric constant restricts the improvement of their energy storage density, which is also not conducive to their application in high pulse power systems; the main advantage of polymer dielectric materials is their high dielectric breakdown field strength, usually greater than 2MV / cm, but their low dielectric constant and problems such as chain breakage, thermal degradation, and discoloration failure caused by ultraviolet radiation in high-temperature outdoor environments also limit their application in extreme environments; compared with the above-mentioned dielectric materials, microcrystalline glass is a type of composite material. By melting powders of certain components into glass and then performing controlled crystallization heat treatment, crystals are precipitated from the glass matrix, thereby obtaining a composite material with both ceramic and glass phases coexisting. Therefore, glass-ceramics have distinct advantages in pulsed power systems operating in extreme environments: First, its base material is glass, and its discharge behavior is similar to that of glass dielectric materials, enabling ultrafast discharge speeds. Second, through compositional design and controlled crystallization, the dielectric constant can be greatly increased, resulting in higher energy density. Furthermore, its excellent UV radiation resistance provides it with a longer service life and environmental adaptability. Furthermore, the stable high energy storage efficiency of glass-ceramics at high field strengths helps reduce energy loss during high-field applications, alleviating heating issues in power devices. Therefore, glass-ceramics has excellent application prospects and development potential in pulsed power technology applications. Summary of the Invention
[0004] In order to solve the above problems, the first aspect of the present invention provides a microcrystalline glass dielectric material with excellent energy storage performance (high energy storage density and high energy storage efficiency) and anti-ultraviolet radiation characteristics (photochromism under ultraviolet irradiation), including a main crystalline phase and a glass phase. The main crystalline phase is precipitated from the glass phase, and nanocrystals with a paraelectric phase structure are formed in the glass phase. The main crystalline phase is a crystalline material with a cubic perovskite structure, which has high energy storage density, ultra-fast charge and discharge speed, high energy storage efficiency under high field strength and good ultraviolet radiation resistance, which greatly improves the energy storage density of the microcrystalline glass dielectric material and the charge and discharge characteristics in extreme environments.
[0005] As a preferred technical solution, the chemical formula of the main crystalline phase is Ba[Ti (1-x) A x ]O3, the chemical formula of the glass phase is SiO2-Al2O3-B2O3; wherein the A element includes at least one or more of the transition metal elements Hf, Zr of group IVB and V, Nb, Ta of group VB.
[0006] As a preferred technical solution, the chemical composition of the microcrystalline glass dielectric material is: Ba[Ti (1-x) A x ]O3-SiO2-Al2O3-B2O3; wherein x is the molar percentage of the transition metal oxide phase in the microcrystalline glass dielectric material, 0≤x≤2%.
[0007] A second aspect of the present invention provides a method for preparing a glass-ceramic dielectric material, comprising the following steps:
[0008] S1, according to Ba[Ti (1-x) A x The ingredients are prepared in the proportion of O3-SiO2-Al2O3-B2O3, ball-milled for 24 hours, dried, placed in a crucible and kept at a melting temperature of 1400-1600°C for 0.5-2 hours to form a uniform glass liquid;
[0009] S2: The glass liquid in step S1 is quickly poured into a metal mold for forming, and then annealed in an annealing furnace at 550-650℃ for 4-10 hours to eliminate stress, and then cut into pieces with an area of 1-2 cm 2 Rectangular glass pieces;
[0010] S3. Heating the glass sheet prepared in step S2 at a heating rate of 3°C / min, keeping it at 610-750°C for 1-4 hours for nucleation, and then continuing to heat it at a heating rate of 3°C / min, keeping it at 800-1000°C for 1-8 hours for crystallization to obtain a microcrystalline glass dielectric material.
[0011] As a preferred technical solution, the annealing temperature in step S2 is 640° C. and the annealing time is 8 hours.
[0012] As a preferred technical solution, in step S3, the nucleation temperature is 710°C and the nucleation time is 2 hours; the first stage crystallization temperature is 875°C and the crystallization time is 2 hours; the second stage crystallization temperature is 925°C and the crystallization time is 1 hour.
[0013] A third aspect of the present invention provides a method for preparing a glass-ceramic dielectric material capable of undergoing electrical testing, comprising the following steps:
[0014] S1, according to Ba[Ti (1-x) A x The ingredients are prepared in the proportion of O3-SiO2-Al2O3-B2O3, ball-milled for 24 hours, dried, placed in a crucible and kept at a melting temperature of 1400-1600°C for 0.5-2 hours to form a uniform glass liquid;
[0015] S2: The glass liquid in step S1 is quickly poured into a metal mold for forming, and then annealed in an annealing furnace at 550-650℃ for 4-10 hours to eliminate stress, and then cut into pieces with an area of 1-2 cm 2 Rectangular glass pieces;
[0016] S3, heating the glass sheet prepared in step S2 at a heating rate of 3°C / min, maintaining the temperature at 610-750°C for 1-4 hours for nucleation, and then continuing to heat at a heating rate of 3°C / min, maintaining the temperature at 800-1000°C for 1-8 hours for crystallization to obtain a microcrystalline glass dielectric material;
[0017] S4. Polish the glass-ceramic dielectric material obtained in step S3 into a thin sheet with a thickness of 0.05-1 mm; screen-print or manually coat the thin sheet with a medium-temperature silver paste, and sinter and solidify it at 600° C. to form a metal silver electrode.
[0018] The photochromic glass-ceramic material with high energy storage efficiency and the preparation method provided by the present invention have the following beneficial effects:
[0019] By adjusting the basic components of glass and the types and contents of transition metal oxides, and using the method of nanodomain engineering, a glass-ceramic with a nano-paraelectric phase structure was precipitated, resulting in a glass-ceramic material with high energy storage density, ultra-fast charge and discharge speed, high energy storage efficiency under high charging field strength, and good UV radiation resistance. The measured discharge energy density of the obtained glass-ceramic material is W d Reaching 12.69J / cm 3 @2100kV / cm; power density P d Reaching 1202MW / cm 3; Recoverable energy storage density W at a field strength of 2100 kV / cm rec Reached 13.32J / cm 3 , and the efficiency η is 92.4%. In addition, compared with traditional polymer dielectrics, the microcrystalline glass material of the present invention still shows good structural and performance stability under ultraviolet radiation. The material sample exhibits obvious photochromism after irradiation with 365nm ultraviolet light, and the color changes from light yellow to black. It can be restored to its original color within a few hours when moved to a dark room. After repeated multiple rounds of cycle testing, the material did not suffer from color fatigue or performance degradation, indicating that it has good ultraviolet response reversibility and anti-radiation stability. This means that the glass ceramic has unique advantages in the application of extreme ultraviolet environments such as space electronic devices, high-power ultraviolet laser capacitors, and national defense weapon systems. At the same time, there is no lead in the glass composition, which achieves the purpose of environmental protection. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is the temperature spectrum data diagram of the microcrystalline glass sample prepared in Example 1.
[0021] Figure 2 This is a graph showing the measured discharge energy density of the glass-ceramic sample prepared in Example 1.
[0022] Figure 3 This is the hysteresis loop data diagram of the microcrystalline glass sample prepared in Example 1.
[0023] Figure 4 This is a comparison chart of the responsiveness and absorption capacity of the glass-ceramic samples prepared in Example 1 to ultraviolet radiation. The area corresponding to number 1 in the figure is the glass-ceramic sample that has not been irradiated with 365nm ultraviolet light, and the area corresponding to number 2 is the glass-ceramic sample that has been irradiated with 365nm ultraviolet light for 30 seconds.
[0024] Figure 5 This is the temperature spectrum data diagram of the microcrystalline glass sample prepared in Example 2.
[0025] Figure 6 This is a graph showing the measured discharge energy density of the glass-ceramic sample prepared in Example 2.
[0026] Figure 7 This is the hysteresis loop data diagram of the microcrystalline glass sample prepared in Example 2.
[0027] Figure 8 This is a comparison chart of the responsiveness and absorption capacity of the glass-ceramics samples prepared in Example 2 to ultraviolet radiation. The area corresponding to number 1 in the figure is the glass-ceramics sample that has not been irradiated with 365nm ultraviolet light, and the area corresponding to number 2 is the glass-ceramics sample that has been irradiated with 365nm ultraviolet light for 30 seconds.
[0028] Figure 9This is the temperature spectrum data diagram of the microcrystalline glass sample prepared in Example 3.
[0029] Figure 10 This is a graph showing the measured discharge energy density of the glass-ceramic sample prepared in Example 3.
[0030] Figure 11 This is the hysteresis loop data diagram of the microcrystalline glass sample prepared in Example 3.
[0031] Figure 12 This is a comparison chart of the responsiveness and absorption capacity of the glass-ceramics samples prepared in Example 3 to ultraviolet radiation. The area corresponding to number 1 in the figure is the glass-ceramics sample that has not been irradiated with 365nm ultraviolet light, and the area corresponding to number 2 is the glass-ceramics sample that has been irradiated with 365nm ultraviolet light for 30 seconds. DETAILED DESCRIPTION
[0032] The technical solution of the present invention is described in detail below with reference to the accompanying drawings and specific embodiments, but the protection scope of the present invention is not limited to the embodiments.
[0033] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs. If the definition of a specific term disclosed in the prior art is inconsistent with any definition provided herein, the definition of the term provided herein shall prevail.
[0034] As used herein, unless the context clearly indicates otherwise, features that are not limited to the singular or plural form are also intended to include features in the plural form. It should also be understood that the term "prepared by..." as used herein is synonymous with "comprising", "including", "including", "having", "containing" and / or "containing", when used in this specification, represents the stated composition, step, method, product or device, but does not exclude the presence or addition of one or more other compositions, steps, methods, products or devices. In addition, when describing embodiments of the present invention, the use of "preferred", "preferably", "more preferred" and the like refers to embodiments of the present invention that may provide certain beneficial effects in certain circumstances. However, other embodiments may also be preferred under the same circumstances or other circumstances. In addition, the statement of one or more preferred embodiments does not imply that other embodiments are not available, nor is it intended to exclude other embodiments from the scope of the present invention.
[0035] To solve the above problems, the first aspect of the present invention provides a photochromic microcrystalline glass material with high energy storage efficiency, including a main crystalline phase and a glass phase. The main crystalline phase is precipitated from the glass phase, and nanocrystals with a paraelectric phase structure are formed in the glass phase. The main crystalline phase is a crystalline material with a cubic perovskite structure, which has high energy storage density, ultra-fast charge and discharge speed, high energy storage efficiency under high charging field strength, and good ultraviolet radiation resistance, which greatly improves the energy storage density of the microcrystalline glass dielectric material and the charge and discharge characteristics in extreme environments.
[0036] In some preferred embodiments, the chemical formula of the main crystalline phase is Ba[Ti (1-x) A x ]O3, the chemical formula of the glass phase is SiO2-Al2O3-B2O3; wherein the A element includes at least one or more of the transition metal elements Hf, Zr of group IVB and V, Nb, Ta of group VB.
[0037] As a preferred technical solution, the chemical composition of the microcrystalline glass material is: Ba[Ti (1-x) A x ]O3-SiO2-Al2O3-B2O3; wherein x is the molar percentage of the transition metal oxide phase in the microcrystalline glass material, 0≤x≤2%.
[0038] For the above-mentioned main crystalline phase and glass phase materials, by adding transition metal oxides, high-temperature melting, heat treatment, nucleation, and crystallization, a high-dielectric and high-energy storage relaxor ferroelectric microcrystalline glass material is obtained. Compared with the prior art, the present invention selects raw materials in a specific proportion, and through the regulation of transition metal oxides, the main crystalline phase is precipitated from the glass phase matrix, so that the glass realizes the precipitation of nanocrystals with a paraelectric phase structure during the crystallization process, and finally obtains a microcrystalline glass dielectric material with high energy storage density, high energy storage efficiency and ultraviolet radiation photochromism. In addition, the matrix material of the present invention is a glass material, and its discharge behavior is similar to that of a glass dielectric, which can obtain an ultra-fast discharge speed; on the other hand, the dielectric constant can be widely regulated and the breakdown field strength can be greatly improved through component design and controllable crystallization; in addition, the good ultraviolet radiation resistance makes it have a longer service life and environmental adaptability. These characteristics ensure that the microcrystalline glass has high energy storage density, ultra-fast charge and discharge speed, high energy storage efficiency under high field strength and good ultraviolet radiation resistance, greatly improving the energy storage density of the microcrystalline glass dielectric material and the charge and discharge characteristics in extreme environments.
[0039] A second aspect of the present invention provides a method for preparing a glass-ceramic material, comprising the following steps:
[0040] S1, according to Ba[Ti (1-x) Ax The ingredients are prepared in the proportion of O3-SiO2-Al2O3-B2O3, ball-milled for 24 hours, dried, placed in a crucible and kept at a melting temperature of 1400-1600°C for 0.5-2 hours to form a uniform glass liquid;
[0041] S2: The glass liquid in step S1 is quickly poured into a metal mold for forming, and then annealed in an annealing furnace at 550-650℃ for 4-10 hours to eliminate stress, and then cut into pieces with an area of 1-2 cm 2 Rectangular glass pieces;
[0042] S3. Heating the glass sheet prepared in step S2 at a heating rate of 3°C / min, keeping it at 610-750°C for 1-4 hours for nucleation, and then continuing to heat it at a heating rate of 3°C / min, keeping it at 800-1000°C for 1-8 hours for crystallization to obtain a microcrystalline glass dielectric material.
[0043] In some preferred embodiments, the annealing temperature in step S2 is 640° C. and the annealing time is 8 hours.
[0044] In some preferred embodiments, in step S3, the nucleation temperature is 710°C, and the nucleation time is 2 hours; the first stage crystallization temperature is 875°C, and the crystallization time is 2 hours; the second stage crystallization temperature is 925°C, and the crystallization time is 1 hour.
[0045] A third aspect of the present invention provides a method for preparing a glass-ceramic dielectric material capable of undergoing electrical testing, comprising the following steps:
[0046] S1, using analytically pure (purity ≥ 99%) BaCO3, H3BO3, Al2O3, TiO2, SiO2, and high purity (99.99%) transition metal oxides as starting materials, according to Ba[Ti (1-x) A x These raw materials are wet-milled in a ball mill for 24 hours, dried, placed in a crucible and kept at a melting temperature of 1400-1600°C for 0.5-2 hours, preferably at a melting temperature of 1550°C for 2 hours, to form a uniform glass liquid;
[0047] S2: The glass liquid in step S1 is quickly poured into a metal mold for forming, and then annealed in an annealing furnace at 550-650℃ for 4-10 hours to eliminate stress, and then cut into pieces with an area of 1-2 cm 2 The rectangular glass sheet preferably has an annealing temperature of 640°C and an annealing time of 8 hours;
[0048] S3, heating the glass sheet prepared in step S2 at a heating rate of 3°C / min, and keeping the temperature at 610-750°C for 1-4 hours for nucleation, preferably the nucleation temperature is 710°C and the nucleation time is 2 hours; continuing to heat at a heating rate of 3°C / min, and keeping the temperature at 800-1000°C for 1-8 hours for crystallization, preferably the crystallization process is as follows: the first stage crystallization temperature is 875°C and the crystallization time is 2 hours; the second stage crystallization temperature is 925°C and the crystallization time is 1 hour, and the main crystal phase is Ba[Ti (1-x) A x ]O3 microcrystalline glass dielectric material with a polycrystalline structure.
[0049] In some preferred embodiments, the grinding balls are yttria or zirconia balls, and the ball milling medium is anhydrous ethanol or deionized water.
[0050] In some preferred embodiments, the forming metal mold is made of copper and has a rectangular or circular shape.
[0051] The third aspect of the present invention provides a method for preparing a microcrystalline glass dielectric material that can be electrically tested, wherein the microcrystalline glass dielectric material obtained in step S3 is polished into a thin sheet with a thickness of 0.05-1 mm; the thin sheet is screen-printed or manually coated with a medium-temperature silver paste, and sintered and solidified at 600°C to form a metal silver electrode.
[0052] The present invention is described in detail below by way of examples. It is necessary to point out that the following examples are only used to further illustrate the present invention and are not to be construed as limiting the scope of protection of the present invention. Any non-essential improvements and adjustments made by professionals in this field based on the above-mentioned contents of the present invention still fall within the scope of protection of the present invention.
[0053] In addition, unless otherwise stated, all raw materials used were commercially available.
[0054] Example
[0055] Example 1 :
[0056] Example 1 provides a photochromic glass-ceramic material with high energy storage efficiency, the chemical composition of which is Ba[Ti (1-x) A x ]O3-SiO2-Al2O3-B2O3, wherein A is Zr element, the doped transition metal oxide is ZrO2, x = (0.1, 0.3, 0.7, 1.5)%.
[0057] Example 1 also provides a preparation method thereof, comprising the following steps:
[0058] S1, using analytically pure (purity ≥ 99%) BaCO3, H3BO3, Al2O3, TiO2, SiO2, and high purity (99.99%) ZrO2 as starting materials, according to Ba[Ti (1-x) Zr x ]O3-SiO2-Al2O3-B2O3 ingredients, where x = (0.1, 0.3, 0.7, 1.5)%; these raw materials are wet-milled in a ball mill for 24 hours, dried, placed in a crucible at 1550°C for 2 hours, and melted into a uniform glass liquid;
[0059] S2: The glass liquid in step S1 is quickly poured into a metal mold for forming, and then annealed in an annealing furnace at 640°C for 8 hours to eliminate stress, and then cut into pieces with an area of 1 to 2 cm 2 Rectangular glass pieces;
[0060] S3, heating the glass sheet prepared in step S2 at a heating rate of 3°C / min, and keeping it at 710°C for 2 hours for nucleation; continuing to heat it at a heating rate of 3°C / min, and keeping it at 875°C for 2 hours for the first stage of crystallization; continuing to heat it at a heating rate of 3°C / min, and keeping it at 925°C for 1 hour for the second stage of crystallization, to obtain a main crystalline phase of Ba[Ti (1-x) Zr x ]O3 glass-ceramic dielectric material;
[0061] S4, processing the glass-ceramic material slice obtained in S3 and polishing it into a slice with a thickness of 0.05 mm;
[0062] S5. The microcrystalline glass slices obtained in S4 are screen-printed or manually coated with medium-temperature silver paste (Guiyan Platinum Industry), and sintered and solidified at 600°C to form metal silver electrodes, thereby obtaining a relaxor ferroelectric microcrystalline glass dielectric material that can be electrically tested.
[0063] After testing, the temperature spectrum of the glass-ceramic material when x=0.3 is as follows Figure 1 As shown, the Δε of the sample is calculated r ≤±15%, showing good temperature stability. The measured discharge energy density of the glass-ceramic can reach 8.92J / cm 3 @1800kV / cm(such as Figure 2 As shown), the discharge power density can reach 750MW / cm 3 (like Figure 2 As shown), the recoverable energy storage density can reach 9.42J / cm 3 @1800kV / cm and the energy storage efficiency is 92.2% (such as Figure 3and under 365nm ultraviolet irradiation, after no less than 20 light-dark cycle experiments, the sample showed good color change repeatability and physical integrity, and no microcracks, peeling or structural damage was observed (the photochromic effect showing radiation absorption characteristics is shown in Figure 1). Figure 4 (As shown in Area 2 in the figure, Area 1 is the area not irradiated by UV light). Test conditions: Temperature spectrum (Agilent E4294A LCR meter, USA) to measure the changes in dielectric properties as a function of temperature and frequency; hysteresis loop (Radiant ferroelectric tester, USA); charge-discharge test system (voltage 10kV, load 200Ω, domestic charge-discharge test system, the test principle is to use an RLC oscillation circuit to measure the change in discharge current over time after the dielectric material is charged and calculate the energy storage density and power density); photochromic excitation light source (China SupFire ultraviolet lamp, wavelength 365nm, power 12W).
[0064] Example 2 :
[0065] Example 2 provides a photochromic glass-ceramic material with high energy storage efficiency, the chemical composition of which is Ba[Ti (1-x) A x ]O3-SiO2-Al2O3-B2O3, wherein A is Hf element, the doped transition metal oxide is HfO2, and x = (0.05, 0.1, 0.3, 0.5)%.
[0066] Example 2 also provides a preparation method thereof, comprising the following steps:
[0067] S1, using analytically pure (purity ≥ 99%) BaCO3, H3BO3, Al2O3, TiO2, SiO2, and high purity (99.99%) HfO2 as starting materials, according to Ba[Ti (1-x) Hf x ]O3-SiO2-Al2O3-B2O3 ingredients, where x = (0.05, 0.1, 0.3, 0.5)%; these raw materials are wet-milled in a ball mill for 24 hours, dried, placed in a crucible at 1550°C for 2 hours, and melted into a uniform glass liquid;
[0068] S2: The glass liquid in step S1 is quickly poured into a metal mold for forming, and then annealed in an annealing furnace at 640°C for 8 hours to eliminate stress, and then cut into pieces with an area of 1 to 2 cm 2 Rectangular glass pieces;
[0069] S3, heating the glass sheet prepared in step S2 at a heating rate of 3°C / min, and keeping it at 710°C for 2 hours for nucleation; continuing to heat it at a heating rate of 3°C / min, and keeping it at 875°C for 2 hours for the first stage of crystallization; continuing to heat it at a heating rate of 3°C / min, and keeping it at 925°C for 1 hour for the second stage of crystallization, to obtain a main crystalline phase of Ba[Ti (1-x) Hf x ]O3 glass-ceramic dielectric material;
[0070] S4, processing the glass-ceramic material slice obtained in S3 and polishing it into a slice with a thickness of 0.05 mm;
[0071] S5. The microcrystalline glass slices obtained in S4 are screen-printed or manually coated with medium-temperature silver paste (Guiyan Platinum Industry), and sintered and solidified at 600°C to form metal silver electrodes, thereby obtaining a relaxor ferroelectric microcrystalline glass dielectric material that can be electrically tested.
[0072] After testing, the temperature spectrum of the glass-ceramic material when x=0.3 is as follows Figure 5 As shown, the Δε of the sample is calculated r ≤±15%, showing good temperature stability. The measured discharge energy density of the glass-ceramic can reach 7.3J / cm 3 @1800kV / cm(such as Figure 6 As shown), the discharge power density can reach 548MW / cm 3 (like Figure 6 As shown), the recoverable energy storage density can reach 9.76J / cm 3 @1800kV / cm and energy storage efficiency is 90% (such as Figure 7 As shown), and under 365nm ultraviolet irradiation, after no less than 20 light-dark cycle experiments, the sample showed good color change repeatability and physical integrity, and no microcracks, peeling or structural damage was observed (the photochromic effect showing radiation absorption characteristics is shown as Figure 8 As shown in area 2 in the figure, area 1 is the area not irradiated by ultraviolet light).
[0073] Example 3 :
[0074] Example 3 provides a photochromic glass-ceramic material with high energy storage efficiency, the chemical composition of which is Ba[Ti (1-x) A x ]O3-SiO2-Al2O3-B2O3, where A is two elements Hf and Zr, the doped transition metal oxides are HfO2 and ZrO2, and x = 0.7%.
[0075] Example 3 also provides a preparation method thereof, comprising the following steps:
[0076] S1, using analytically pure (purity ≥ 99%) BaCO3, H3BO3, Al2O3, TiO2, SiO2, and high purity (99.99%) HfO2 and ZrO2 as starting materials, according to Ba[Ti 0.993 (Zr (1-y) Hf y ) 0.007 ]O3-SiO2-Al2O3-B2O3 ingredients, where y = (0.3, 0.5, 0.7)%; these raw materials are wet-milled in a ball mill for 24 hours, dried, placed in a crucible at 1550°C for 2 hours, and melted into a uniform glass liquid;
[0077] S2: The glass liquid in step S1 is quickly poured into a metal mold for forming, and then annealed in an annealing furnace at 640°C for 8 hours to eliminate stress, and then cut into pieces with an area of 1 to 2 cm 2 Rectangular glass pieces;
[0078] S3, heating the glass sheet prepared in step S2 at a heating rate of 3°C / min, keeping the temperature at 710°C for 2h for nucleation; continuing to heat at a heating rate of 3°C / min, keeping the temperature at 875°C for 2h for the first stage of crystallization; continuing to heat at a heating rate of 3°C / min, keeping the temperature at 925°C for 1h for the second stage of crystallization, and obtaining a main crystalline phase of Ba[Ti 0.993 (Zr (1-y) Hf y ) 0.007 ]O3 glass-ceramic dielectric material;
[0079] S4, processing the glass-ceramic material slice obtained in S3 and polishing it into a slice with a thickness of 0.05 mm;
[0080] S5. The microcrystalline glass slices obtained in S4 are screen-printed or manually coated with medium-temperature silver paste (Guiyan Platinum Industry), and sintered and solidified at 600°C to form metal silver electrodes, thereby obtaining a relaxor ferroelectric microcrystalline glass dielectric material that can be electrically tested.
[0081] After testing, the temperature spectrum of the glass-ceramic material when y=0.33 is as follows Figure 9 As shown, the Δε of the sample is calculated r ≤±15%, showing good temperature stability. The measured discharge energy density of the glass-ceramic can reach 12.69J / cm 3 @2100kV / cm(such as Figure 10 As shown), the discharge power density can reach 1202MW / cm 3 (like Figure 10 As shown), the recoverable energy storage density can reach 13.32J / cm 3@2100kV / cm and the energy storage efficiency is 92.4% (such as Figure 11 As shown), and under 365nm ultraviolet irradiation, after no less than 20 light-dark cycle experiments, the sample showed good color change repeatability and physical integrity, and no microcracks, peeling or structural damage was observed (the photochromic effect showing radiation absorption characteristics is shown as Figure 12 As shown in area 2 in the figure, area 1 is the area not irradiated by ultraviolet light).
[0082] Although embodiments of the present invention have been shown and described, it will be apparent to those skilled in the art that various changes, modifications, substitutions and variations may be made to these embodiments without departing from the principles and spirit of the present invention. The scope of protection of the present invention is defined by the appended claims and their equivalents.
Claims
1. A photochromic glass-ceramic material with high energy storage efficiency, characterized by: It includes a main crystal phase and a glass phase. The main crystal phase is precipitated from the glass phase, and nanocrystals with a paraelectric phase structure are obtained in the glass phase. The main crystal phase is a crystal material with a cubic perovskite structure.
2. The glass-ceramic material according to claim 1, wherein: The chemical formula of the main crystalline phase is Ba[Ti (1-x) A x ]O3, the chemical formula of the glass phase is SiO2-Al2O3-B2O3; wherein the A element includes at least one of the transition metal elements Hf, Zr of group IVB and V, Nb, Ta of group VB, and a combination of several of them.
3. The glass-ceramic material according to claim 2, wherein: The chemical composition of the microcrystalline glass material is: Ba[Ti (1-x) A x ]O3-SiO2-Al2O3-B2O3; wherein x is the molar percentage of the transition metal oxide phase in the microcrystalline glass material, 0≤x≤2%.
4. A method for preparing a glass-ceramic material according to any one of claims 1 to 3, characterized in that: The steps include: S1, according to Ba[Ti (1-x) A x The ingredients are prepared in the proportion of O3-SiO2-Al2O3-B2O3, ball-milled for 24 hours, dried, placed in a crucible and kept at a melting temperature of 1400-1600°C for 0.5-2 hours to melt into a uniform glass liquid; S2: The glass liquid in step S1 is quickly poured into a metal mold for forming, and then annealed in an annealing furnace at 550℃-650℃ for 4h-10h to eliminate stress and then cut into pieces with an area of 1cm 2 ~2cm 2 Rectangular glass pieces; S3. Heating the glass sheet prepared in step S2 at a heating rate of 3°C / min, keeping it at 650°C-750°C for 1h-4h for nucleation, and then continuing to heat it at a heating rate of 3°C / min, keeping it at 800°C-1000°C for 1h-8h for crystallization to obtain a microcrystalline glass dielectric material.
5. The method for preparing a glass-ceramic material according to claim 4, wherein: The annealing temperature in step S2 is 640° C., and the annealing time is 8 hours.
6. The method for preparing a glass-ceramic material according to claim 4, wherein: In step S3, the nucleation temperature is 710° C. and the nucleation time is 2 h; the first stage crystallization temperature is 875° C. and the crystallization time is 2 h; the second stage crystallization temperature is 925° C. and the crystallization time is 1 h.
7. A method for preparing a glass-ceramic material capable of electrical testing, characterized in that: The following steps are involved: S1, according to Ba[Ti (1-x) A x The ingredients are prepared in the proportion of O3-SiO2-Al2O3-B2O3, ball-milled for 24 hours, dried, placed in a crucible and kept at a melting temperature of 1400-1600°C for 0.5-2 hours to melt into a uniform glass liquid; S2: The glass liquid in step S1 is quickly poured into a metal mold for forming, and then annealed in an annealing furnace at 550℃-650℃ for 4-10 hours to eliminate stress, and then cut into pieces with an area of 1cm 2 ~2cm 2 Rectangular glass pieces; S3. Heating the glass sheet prepared in step S2 at a heating rate of 3°C / min, keeping it at 650°C-750°C for 1-4 hours for nucleation, and then continuing to heat it at a heating rate of 3°C / min, keeping it at 800°C-1000°C for 1 hour-8 hours for crystallization to obtain a microcrystalline glass dielectric material. S4. Polish the glass-ceramic material obtained in step S3 into a thin sheet with a thickness of 0.05 mm to 1 mm; screen-print or manually coat the thin sheet with a medium-temperature silver paste, and sinter and solidify it at 600° C. to form a metal silver electrode.